GEOMATICS ACCURACY AND PRECISION OF DETERMINATION HORIZONTAL DISTANCES IN STAKE OUT MEASUREMENT USING THEODOLITE - Totok Sulistyo; Karmila Achmad; Rahmad Bangun Giarto (P3M- Politeknik Negeri Kupang, 2019)
Stake-Out is a processes of transferring construction design to the real world so that Stake Out is highly imperative in a construction job. Stake-Out jobs in the middle and lower levels of construction industry are still using theodolite accompanying with calculator rather than using high-end instruments. The results of the study show that theodolite has lower accuracy compared to Total Station and other high-end instruments, such as GPS Geodetic and Laser Scanner. This research is aimed to determine the accuracy and precision of Theodolite in determining the horizontal distance of Stake Out measurement which staff reading is simulated using android App (Stake Out Guide). The results of experiment showed that the accuracy of Theodolite is 0.025 m meanwhile the precision is 0.12%.